Poly (cobalt phthalocyanine) with defect structure and preparation method and application of poly (cobalt phthalocyanine)
The formation of polyphthalocyanine cobalt with defective structures through hydrothermal reactions solves the problem of insufficient catalytic performance of existing polyphthalocyanine cobalt, improves the degradation efficiency of organic pollutants, and realizes environmentally friendly and low-cost wastewater treatment.
Patent Information
- Application Number
- CN202411043267.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-07-31
AI Technical Summary
The existing polyphthalocyanine cobalt catalytic performance is insufficient, resulting in its low efficiency in degrading organic pollutants in advanced oxidation water treatment, and the modification method is complex and may introduce environmental pollution.
By using a hydrothermal reaction method, polyphthalocyanine cobalt and water are mixed with water at 140°C to 185°C to form polyphthalocyanine cobalt with defective structure, increasing its pore structure and specific surface area, and promoting electron transfer and adsorption of pollutants.
It improves the exposure and electron transfer efficiency of catalytically active sites, enhances the degradation ability of organic pollutants, and has a simple and environmentally friendly process, which is suitable for wastewater treatment.
Smart Images

Figure CN119119463A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of advanced oxidation water treatment, and in particular relates to polycobalt phthalocyanine with a defective structure and a preparation method and application thereof. Background Art
[0002] As an advanced oxidation process, persulfate oxidation not only has the advantages of high efficiency, easy storage, easy transportation, low cost and excellent stability, but also can effectively overcome the limitation of the traditional Fenton method that reacts in a narrow pH range. That is, the Fenton method needs to be in acidic conditions to achieve the best effect, while the persulfate oxidation method can react efficiently in a wider pH range, has stronger adaptability, and can be applied to different environmental conditions. These characteristics make persulfate perform well in treating various organic pollutants, especially in the fields of wastewater treatment, soil remediation and groundwater purification. In recent years, the persulfate oxidation method has received more and more attention and has become a research hotspot in the field of environmental catalysis.
[0003] Polyphthalocyanine cobalt is polymerized from cobalt phthalocyanine monomers. The cobalt phthalocyanine monomers consist of a metal cobalt center and four isoindole subunits, have 18 π electrons, and are widely used in various catalytic processes. Theoretical studies have shown that the strong electronegativity of the nitrogen atom in the phthalocyanine ring can regulate the electron cloud density of the adjacent atoms, form metal-nitrogen active sites, and promote the adsorption of reactants. In addition, the unsaturated low-coordination environment between the central metal cobalt ion and the four isoindole subunits gives the metal center a high catalytic activity. However, the π-π stacking structure between cobalt phthalocyanine molecules will lead to shielding of the active sites, limit the axial transfer of electrons, and thus inhibit the catalytic reaction. Therefore, it is necessary to further modify cobalt phthalocyanine to improve its catalytic performance. At present, the method to improve the catalytic performance of cobalt phthalocyanine is usually to introduce new functional groups or load it on other carriers, which will increase the cost of preparation and potential environmental pollution problems. Therefore, finding a simple and green preparation method to obtain cobalt phthalocyanine with defective structure has broad practical significance for effectively activating persulfate and efficiently degrading organic pollutants. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a polyphthalocyanine cobalt with a defective structure having a rich pore structure, a large specific surface area, more exposed active sites, fast electron transfer efficiency, and good recyclability, as well as a preparation method and application thereof.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions.
[0006] A method for preparing polycobalt phthalocyanine with a defective structure comprises the following steps: mixing polycobalt phthalocyanine with water, and performing a hydrothermal reaction at 140° C. to 185° C. to obtain polycobalt phthalocyanine with a defective structure.
[0007] The above preparation method is further improved in that the temperature of the hydrothermal reaction is 175°C to 185°C.
[0008] The above preparation method is further improved in that the time of the hydrothermal reaction is 4h to 8h, and the heating rate during the hydrothermal reaction is 2°C / min to 8°C / min.
[0009] The above preparation method is further improved, and the preparation method of polycobalt phthalocyanine comprises the following steps: mixing pyromellitic anhydride, urea, ammonium chloride, ammonium molybdate and cobalt chloride, and performing polymerization reaction at 210° C. to 230° C. to obtain polycobalt phthalocyanine.
[0010] The above preparation method is further improved, wherein the mass ratio of the pyromellitic anhydride, urea, ammonium chloride, ammonium molybdate and cobalt chloride is 1-1.1: 2-2.1: 0.4-0.6: 0.002-0.003: 0.5-0.55, the heating rate during the polymerization reaction is 3°C / min-10°C / min, the polymerization reaction time is 2.5h-3.5h, and the polymerization reaction also includes the following treatments after the polymerization reaction: grinding, washing and drying the reaction product; the washing is washing with water and anhydrous ethanol in sequence, and the drying is vacuum drying at 60°C for 12h.
[0011] The above preparation method is further improved, wherein the ratio of the polyphthalocyanine cobalt to water is 200 mg to 300 mg: 30 mL to 50 mL, the mixing time is 15 min to 25 min, and the mixing is carried out under stirring conditions; the hydrothermal reaction also includes the following treatments: washing and drying the reaction product; the washing is carried out using water or anhydrous ethanol, and the drying is carried out under vacuum at 60°C for 12 hours.
[0012] As a general technical concept, the present invention also provides a polycobalt phthalocyanine with a defective structure obtained by the above-mentioned preparation method.
[0013] As a general technical concept, the present invention also provides an application of the above-mentioned poly(cobalt phthalocyanine) with defective structure in treating wastewater containing organic pollutants.
[0014] The above application is further improved, comprising the following steps: mixing polyphthalocyanine cobalt with defective structure and organic pollutant wastewater, adding persulfate to carry out degradation reaction, and realizing degradation of organic pollutants in water; the ratio of polyphthalocyanine cobalt with defective structure to organic pollutant wastewater is 0.03g-0.2g:1L.
[0015] The above application is further improved, wherein the amount of persulfate added is 0.75 mmol to 1.25 mmol per liter of organic pollutant wastewater, the persulfate is potassium persulfate, the concentration of organic pollutants in the organic pollutant wastewater is ≤20 mg / L, the pH value of the organic pollutant wastewater is 3 to 11, the organic pollutants in the organic pollutant wastewater include at least one of antibiotics and dyes, the antibiotic is at least one of tetracycline hydrochloride, levofloxacin hydrochloride, ciprofloxacin and phenol, the dye is at least one of rose red B and methylene blue, the degradation reaction time is ≥5 min, the degradation reaction is carried out under stirring conditions, and the stirring speed is 300 rpm to 500 rpm.
[0016] Compared with the prior art, the advantages of the present invention are:
[0017] (1) In view of the defects of the current polyphthalocyanine cobalt modification process, such as complex process, easy introduction of other chemical substances and carriers leading to increased costs and environmental pollution, the present invention provides a method for preparing polyphthalocyanine cobalt with a defective structure constructed by a simple hydrothermal reaction, that is, mixing polyphthalocyanine cobalt with water, and performing a hydrothermal reaction at 140°C to 185°C to obtain polyphthalocyanine cobalt with a defective structure. The polyphthalocyanine cobalt with a defective structure of the present invention forms defects on the molecular plane of polyphthalocyanine cobalt at high temperature through a hydrothermal reaction. On the one hand, the defective structure can increase the pores and specific surface area of the catalyst material, thereby increasing the exposed active sites; on the other hand, the defective position can serve as a channel for electron transfer to promote electron transfer; at the same time, graphite carbon, graphite nitrogen, carbonyl and other structures are formed in the hydrothermal modification process, which can serve as active sites for persulfate adsorption and activation, thereby enhancing the removal effect of pollutants. The polyphthalocyanine cobalt with defective structure of the present invention has the advantages of rich pore structure, large specific surface area, more exposed active sites, fast electron transfer efficiency, good recyclability, etc., can effectively activate percarbonate, and achieve efficient degradation of organic pollutants by combining a dual non-free radical (singlet oxygen and high-valent metal oxygen) as the leading and free radical (sulfate radical) as the auxiliary. The preparation method of the present invention has the advantages of simple process, convenient operation, low cost, green environmental protection, etc., provides a new idea for the modification and design of organic high molecular polymers, and has certain practical application significance for the repair and treatment of difficult-to-degrade organic pollutants in wastewater.
[0018] (2) The preparation method of the present invention can obtain polyphthalocyanine cobalt with a defective structure having higher catalytic activity by optimizing the temperature of the hydrothermal reaction to 175°C to 185°C. When the hydrothermal reaction temperature is too low, the defective structure and graphitic nitrogen cannot be formed or the amount is small; when the hydrothermal reaction temperature is too high, the hydrothermal reaction will be unstable and there is a risk of explosion.
[0019] (3) The present invention also provides an application of polyphthalocyanine cobalt with a defective structure in treating organic pollutant wastewater. The polyphthalocyanine cobalt with a defective structure is mixed with organic pollutant wastewater, and persulfate is added for catalytic reaction, so that the organic pollutants in the water body can be effectively degraded. There are multiple degradation mechanisms in the degradation system of polyphthalocyanine cobalt with a defective structure / persulfate of the present invention, namely, the double non-radical pathway of singlet oxygen and high-valent metal oxygen is the main one, and sulfate radical is the auxiliary one, so that a high organic pollutant removal rate is shown. Specifically, the life span of non-radicals is longer than that of free radicals, which improves the efficiency of active oxygen, and they have strong anti-interference ability to the environment, can maintain efficient degradation of organic pollutants in a wide pH range, and have strong resistance to the adverse effects of various ions in the water body. It has the advantages of simple operation, good degradation effect, low cost, etc., and is suitable for practical application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 SEM images of cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, cobalt polyphthalocyanine with a defect structure (D-CoPPc-180), modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2.
[0021] Figure 2 XRD patterns of cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, cobalt polyphthalocyanine with defect structure (D-CoPPc-180), modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2.
[0022] Figure 3 Isothermal adsorption-desorption curves of cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, cobalt polyphthalocyanine with defect structure (D-CoPPc-180), modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2.
[0023] Figure 4 The pore size distribution diagrams are of cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, cobalt polyphthalocyanine with defect structure (D-CoPPc-180), modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2.
[0024] Figure 5Raman spectra of cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, cobalt polyphthalocyanine with defect structure (D-CoPPc-180), modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2.
[0025] Figure 6 The Raman spectra of the cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, the cobalt polyphthalocyanine with defect structure (D-CoPPc-180), the modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and the modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2 are in the range of 1200-1700 cm -1 Peak separation diagram at wavelength.
[0026] Figure 7 It is the full XPS spectra of the cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, the cobalt polyphthalocyanine with defect structure (D-CoPPc-180), the modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and the modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2.
[0027] Figure 8 N1s peak diagrams of cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, cobalt polyphthalocyanine with defect structure (D-CoPPc-180), modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2.
[0028] Fig. 9 Infrared spectra of cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, cobalt polyphthalocyanine with defect structure (D-CoPPc-180), modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2.
[0029] Fig.10 This is a diagram showing the effects of poly(cobalt phthalocyanine) (CoPPc), poly(cobalt phthalocyanine) with a defective structure (D-CoPPc-180), modified poly(cobalt phthalocyanine) (D-CoPPc-100), and modified poly(cobalt phthalocyanine) (D-CoPPc-140) in Example 2 of the present invention on the degradation of tetracycline hydrochloride.
[0030] Fig.11 This is a graph showing the degradation of tetracycline hydrochloride by cobalt polyphthalocyanine (D-CoPPc-180) with a defective structure under different pH conditions in Example 3 of the present invention.
[0031] Fig.12This is a diagram showing the degradation effect of cobalt polyphthalocyanine (D-CoPPc-180) with a defective structure on different pollutants in Example 4 of the present invention. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby. The materials and instruments used in the following embodiments are all commercially available.
[0033] Embodiment 1:
[0034] A method for preparing polycobalt phthalocyanine with a defective structure of the present invention comprises the following steps:
[0035] (1) Weigh 1.05 g of pyromellitic anhydride, 2.05 g of urea, 0.5 g of ammonium chloride, 0.00225 g of ammonium molybdate, and 0.528 g of cobalt chloride in a mortar, grind and mix them evenly by hand, transfer them to a crucible after grinding, and wrap them with tin foil; transfer the crucible to a muffle furnace, heat it to 220°C at a heating rate of 3°C / min, keep it for 3 h, and take it out after the muffle furnace is cooled to room temperature; grind the reaction product into powder with a mortar, and filter and wash it three times with ultrapure water and anhydrous ethanol respectively, and dry it in vacuum at 60°C for 12 h to obtain cobalt polyphthalocyanine, denoted as CoPPc.
[0036] (2) Weigh 200 mg of the cobalt polyphthalocyanine powder obtained in step (1) on an analytical balance and place it in a Teflon liner. Add 30 mL of deionized water and stir vigorously for 20 min. Seal the liner in a hydrothermal reactor and perform a hydrothermal reaction at 180° C. for 6 hours. After the reactor is cooled to room temperature, take out the product, wash it three times with deionized water, and then dry it in a vacuum drying oven at 60° C. for 12 h to obtain a cobalt polyphthalocyanine with a defective structure, which is recorded as D-CoPPc-180.
[0037] Comparative Example 1:
[0038] A modified cobalt polyphthalocyanine, the preparation method of which is basically the same as the preparation method of the cobalt polyphthalocyanine with a defective structure (D-CoPPc-180) in Example 1, the only difference is that: in step (2), the temperature of the hydrothermal reaction is 100° C.; the modified cobalt polyphthalocyanine obtained is recorded as D-CoPPc-100.
[0039] Comparative Example 2:
[0040] A modified cobalt polyphthalocyanine, the preparation method of which is basically the same as the preparation method of the cobalt polyphthalocyanine with a defective structure (D-CoPPc-180) in Example 1, the only difference being that in step (2), the temperature of the hydrothermal reaction is 140° C.; the modified cobalt polyphthalocyanine obtained is recorded as D-CoPPc-140.
[0041] Figure 1 SEM images of cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, cobalt polyphthalocyanine with a defect structure (D-CoPPc-180), modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2. Figure 1 In the figure, (a), (c), (e), and (g) are SEM images of CoPPc, D-CoPPc-100, D-CoPPc-140, and D-CoPPc-180 magnified 50,000 times, respectively, and (b), (d), (f), and (h) are SEM images of CoPPc, D-CoPPc-100, D-CoPPc-140, and D-CoPPc-180 magnified 5,000 times, respectively. Figure 1 It can be seen that CoPPc, D-CoPPc-100, D-CoPPc-140, and D-CoPPc-180 are generally irregular blocks, and the surface of the original CoPPc is smooth. As the temperature of the hydrothermal reaction increases, the surface wrinkles of the cobalt polyphthalocyanine catalyst increase and become rougher, which increases the specific surface area of the catalyst, thereby exposing more active sites, which is conducive to the adsorption and activation of pollutants and persulfate.
[0042] Figure 2 The XRD patterns of the cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, the cobalt polyphthalocyanine with defect structure (D-CoPPc-180), the modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and the modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2 are shown in FIG. Figure 2It can be seen that due to the different interlayer arrangements, the crystal domains inside CoPPc can be deconvoluted into two π-π stacking crystal forms, namely the uniformly arranged α type and the staggered β type. The characteristic diffraction peaks of the CoPPc sample at 2θ = 17.3°, 18.4°, 18.8°, 27.1°, 29.4° and 30.4° are attributed to the (200), (001), and (101) planes of β-CoPPc, the interlayer stacking of the aromatic system, and the (001) and (101) planes of α-CoPPc, respectively. The XRD spectra of the modified samples are very different from those of the original samples. D-CoPPc-X (X=100, 140, 180) does not inherit the sharp and narrow characteristic diffraction peak of CoPPc, and only retains the diffraction peak of about 27.14°, which indicates that the hydrothermal reaction at high temperature can destroy the crystal structure of CoPPc and transform it into an amorphous property; at the same time, with the increase of the hydrothermal reaction temperature, a new characteristic diffraction peak appears at about 22°, which may be related to the (002) plane reflection of the graphite structure of the carbon material. This shows that a higher hydrothermal reaction temperature can form a graphite phase in the sample, and the graphite phase can serve as a medium for electron transfer and increase the rate of electron transfer.
[0043] Figure 3 Isothermal adsorption-desorption curves of cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, cobalt polyphthalocyanine with defect structure (D-CoPPc-180), modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2. Figure 4 The pore size distribution diagrams are shown for cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, cobalt polyphthalocyanine with defective structure (D-CoPPc-180), modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2. Figure 3 It can be seen that the surface areas of the catalysts are 3.8253 m 2 g -1 (CoPPc), 5.0163m 2 g -1 (D-CoPPc-100), 5.1843m 2 g -1 (D-CoPPc-140), 5.3441m 2 g -1 (D-CoPPc-180), which proves that the surface area of cobalt polyphthalocyanine with defective structure increases with the increase of hydrothermal reaction temperature, which is consistent with the results of SEM images. Figure 4It can be seen that the pore size of each catalyst is distributed around 20 nm, which is mesoporous. It can be seen that the polyphthalocyanine cobalt with defective structure of the present invention has the advantages of large specific surface area and rich pore structure, which is conducive to the exposure of active sites, thereby promoting the adsorption of organic pollutants and improving mass transfer efficiency, and finally effectively promoting the degradation of organic pollutants.
[0044] Figure 5 Raman spectra of cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, cobalt polyphthalocyanine with defect structure (D-CoPPc-180), modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2. Figure 6 The Raman spectra of the cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, the cobalt polyphthalocyanine with defect structure (D-CoPPc-180), the modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and the modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2 are in the range of 1200-1700 cm -1 The peak diagram at different wavelengths. Figure 5 and Figure 6 It can be seen that the Raman spectra of different samples are highly similar, with the peaks at 684, 1454 and 1540 cm -1 A 1g , B 2g and B 1g The bands represent the C–N–C stretching of isoindole, while the bands at 748, 1125, and 1331 cm -1 B1g and two A 1g The bands represent the N–M stretching of isoindole. In addition, at 1350 cm -1 and 1590cm -1 Two distinguishable peaks, D and G, appeared at 1200–1700 cm -1 The peaks of the bands were analyzed and the D and G bands were separated. The ratio of the D peak to the G peak intensity can reflect the degree of catalyst defects. The larger the ratio, the higher the degree of defects. D / I G The ratios are 0.280, 0.275, 0.449, and 0.651, respectively, which indicates that the hydrothermal reaction at 100 °C cannot effectively create defects on the polyphthalocyanine cobalt plane, and defects can only be formed under high-temperature hydrothermal conditions.
[0045] Figure 7It is the full XPS spectra of the cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, the cobalt polyphthalocyanine with defect structure (D-CoPPc-180), the modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and the modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2. Figure 8 The N1s peak diagrams of the cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, the cobalt polyphthalocyanine with defect structure (D-CoPPc-180), the modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and the modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2. Figure 7 and Figure 8 It can be seen that the full spectrum scanning spectra of each catalyst show obvious C, N, O, and Co signals, which are also the main elements of polyphthalocyanine cobalt; it is worth noting that in the high-resolution XPS N 1s spectrum of each sample, the peaks of 399.03eV, 400.10eV and 404.58eV belong to pyridine N, Co-N bond and oxidized N species, respectively. Compared with CoPPc and D-CoPPc-100, the N1s spectra of D-CoPPc-140 and D-CoPPc-180 have a new peak at around 402.00eV, which is attributed to graphitic nitrogen, indicating that graphitic nitrogen is formed in the structure of polyphthalocyanine cobalt under high temperature hydrothermal conditions, and the hydrothermal temperature is proportional to the content of graphitic nitrogen. The defective polyphthalocyanine cobalt (D-CoPPc-180) of the present invention can effectively activate persulfate, because: on the one hand, graphite nitrogen can serve as the main active site for PMS activation. Due to the high electronegativity of graphite N, it can destroy the balance of the nearby sp2 hybridized carbon (graphite carbon) network and promote the transfer of electrons from nearby carbon atoms to nitrogen atoms; on the other hand, PMS molecules have a strong affinity with graphite nitrogen with high electron density and are easily enriched near graphite nitrogen, and then PMS can quickly self-decompose into singlet oxygen.
[0046] Fig. 9 The infrared spectra of the cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, the cobalt polyphthalocyanine with defect structure (D-CoPPc-180), the modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and the modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2 are shown in FIG. Fig. 9 It can be seen that the FT-IR spectra of different materials are roughly the same, with the C–H group at 642–744 cm -1 Swinging and torsional vibrations occur at 1521 and 1612 cm -1 There are CC absorption peaks at 1317 and 1138 cm -1 The carbon-nitrogen double bond (C=N) appears at 1571 cm -1Stretching vibration occurs at 1060-1421 cm -1 The difference is that after hydrothermal modification, the O–H and N–H stretching vibrations of the hydroxyl and amino groups appear at 3120 cm -1 This indicates that the hydrothermal reaction has a positive effect on the formation of new functional groups on the surface of polyphthalocyanine cobalt. In addition, the characteristic peaks corresponding to the carboxylic acid bond and the amide bond appear at 1697 cm -1 and 1680cm -1 These characteristic peaks only appear in the FT-IR spectra of D-CoPPc-140 and D-CoPPc-180. Amide bonds are formed by dehydration condensation of amino and carboxyl groups. When the amino and carboxyl groups come from different polyphthalocyanine molecular planes, the formation of amide bonds can reduce the interlayer distance between the two planes and enhance the interaction between molecules. At the same time, amide bonds can form hydrogen bonds within and between molecules, and hydrogen bonds may also have a positive contribution to intermolecular interactions and electron transfer.
[0047] Embodiment 2:
[0048] An application of the polyphthalocyanine cobalt with a defective structure of the present invention in treating organic pollutant wastewater, specifically using the polyphthalocyanine cobalt with a defective structure to degrade tetracycline hydrochloride (TC) in water, comprises the following steps:
[0049] 5 mg of each of the cobalt polyphthalocyanine (CoPPc) prepared in Example 1 of the present invention, the cobalt polyphthalocyanine with a defective structure (D-CoPPc-180), the modified cobalt polyphthalocyanine (D-CoPPc-100) prepared in Comparative Example 1, and the modified cobalt polyphthalocyanine (D-CoPPc-140) prepared in Comparative Example 2 were added to 100 mL of a tetracycline hydrochloride (TC) solution having a concentration of 10 mg / L and a pH of 4.86; then, 1 mL of a potassium persulfate solution (the concentration of the solution was 100 mM) was added so that the concentration of potassium persulfate (PMS) in the reaction system was 1 mM, and the catalytic reaction was carried out at room temperature and 450 rpm for 60 min to complete the degradation of tetracycline hydrochloride.
[0050] Fig.10 The effect diagram of the degradation of tetracycline hydrochloride by cobalt polyphthalocyanine (CoPPc), cobalt polyphthalocyanine with defective structure (D-CoPPc-180), modified cobalt polyphthalocyanine (D-CoPPc-100), and modified cobalt polyphthalocyanine (D-CoPPc-140) in Example 2 of the present invention is shown. Fig.10It can be seen that with the increase of the hydrothermal reaction temperature, the activation performance of the catalyst for PMS is gradually enhanced, and the removal rate of TC is increased from 68% to 95.9%. Even at a lower hydrothermal reaction temperature (100°C), the activation effect of the catalyst on PMS and the removal rate of TC can be improved. The cobalt polyphthalocyanine (D-CoPPc-180) with defective structure of the present invention removes 95.9% of TC within 60 minutes, because: 1) the surface area of the catalyst increases after modification, exposing more active sites; 2) the formation of defective structure provides a channel for the axial transfer of electrons, promotes the transfer of electrons to PMS, and is beneficial to the activation of PMS; 3) the graphite nitrogen, graphite carbon and a large number of carbonyl groups formed during the modification process can serve as new active sites, enhance the adsorption of pollutants on the catalyst surface, and can also activate PMS to form singlet oxygen and sulfate radicals, thereby showing the highest removal rate of tetracycline hydrochloride (TC).
[0051] Embodiment 3:
[0052] An application of the polyphthalocyanine cobalt with a defective structure of the present invention in treating organic pollutant wastewater, specifically using the polyphthalocyanine cobalt with a defective structure to degrade tetracycline hydrochloride (TC) in water environments with different pH values, comprising the following steps:
[0053] Take 5 cups of 100 mL tetracycline hydrochloride (TC) solution with a concentration of 10 mg / L and a pH of 4.86, and use 0.1 M sulfuric acid and 0.1 M sodium hydroxide solution to adjust the pH of the tetracycline solution to 3, 5, 7, 9, and 11, respectively; then add 5 mg of the cobalt polyphthalocyanine (D-CoPPc-180) with a defective structure prepared in Example 1; then, add 1 mL of potassium persulfate solution (the concentration of the solution is 100 mM) so that the concentration of potassium persulfate (PMS) in the reaction system is 1 mM, and carry out the catalytic reaction at room temperature and 450 rpm for 60 min to complete the degradation of tetracycline hydrochloride.
[0054] Fig.11 The figure is a graph showing the degradation of tetracycline hydrochloride by cobalt polyphthalocyanine (D-CoPPc-180) with defective structure under different pH conditions in Example 3 of the present invention. Fig.11 As shown in the figure, the degradation of TC was significantly inhibited only when the initial pH value was 3, and the degradation of TC was almost unaffected under other pH conditions. In a strong acid environment, the degradation of TC by D-CoPPc-180 was inhibited. The main reasons are: 1) H + and (Introduced when adjusting pH) can react with ·OH and Reaction; 2)H + Can stabilize PMS and hinder its activation; 3)H +It can destroy the active sites and surface functional groups of the catalyst, inhibit the formation of CoOH+ complexes, and make it difficult to activate PMS. In general, the D-CoPPc-180 / PMS system has good adaptability in a wide pH range.
[0055] Embodiment 4:
[0056] An application of the polyphthalocyanine cobalt with a defective structure of the present invention in treating organic pollutant wastewater, specifically using the polyphthalocyanine cobalt with a defective structure to degrade Rose Bengal B (RhB), methylene blue (MB), levofloxacin hydrochloride (LFX), ciprofloxacin (CIP), and phenol (Phenol) in water, comprising the following steps:
[0057] Take 5 portions of cobalt polyphthalocyanine (D-CoPPc-180) with a defective structure prepared in Example 1 of the present invention, 5 mg each, and add them into beakers containing RhB, MB, LFX, CIP, and Phenol solutions, respectively, each containing 100 mL of a pollutant solution with a concentration of 10 mg / L; then, add 1 mL of a potassium persulfate solution (the concentration of the solution is 100 mM) so that the concentration of potassium persulfate (PMS) in the reaction system is 1 mM, and carry out a catalytic reaction at room temperature and 450 rpm for 60 min to complete the degradation of different pollutants.
[0058] Fig.12 The figure is a graph showing the degradation effect of cobalt polyphthalocyanine (D-CoPPc-180) with defective structure on different pollutants in Example 4 of the present invention. Fig.12 It can be seen that the D-CoPPc-180 / PMS system has a high removal efficiency for organic dyes (RhB and MB) and phenols (Phenol), especially RhB and MB, which are completely removed within 5min and 40min, respectively. The degradation efficiency of fluoroquinolones (LXF and CIP) is moderate, and the removal rate remains above 80% within 60 minutes. The difference in the degradation efficiency of different pollutants shows that 1 O2 and Co(IV)=O have selective catalytic properties.
[0059] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as above in the preferred embodiment, it is not used to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing polyphthalocyanine cobalt with defective structure, characterized in that: The following steps are involved: The polyphthalocyanine cobalt and water are mixed and subjected to a hydrothermal reaction at 140° C. to 185° C. to obtain the polyphthalocyanine cobalt with a defect structure.
2. The method for preparing polyphthalocyanine cobalt with defect structure according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 175°C to 185°C.
3. The method for preparing polyphthalocyanine cobalt with defect structure according to claim 2, characterized in that: The time of the hydrothermal reaction is 4 hours to 8 hours, and the heating rate during the hydrothermal reaction is 2° C. / min to 8° C. / min.
4. The method for preparing poly(cobalt phthalocyanine) having a defective structure according to any one of claims 1 to 3, characterized in that: The preparation method of polycobalt phthalocyanine comprises the following steps: mixing pyromellitic anhydride, urea, ammonium chloride, ammonium molybdate and cobalt chloride, and performing polymerization reaction at 210° C. to 230° C. to obtain polycobalt phthalocyanine.
5. The method for preparing polyphthalocyanine cobalt with defect structure according to claim 4, characterized in that: The mass ratio of the pyromellitic anhydride, urea, ammonium chloride, ammonium molybdate and cobalt chloride is 1-1.1: 2-2.1: 0.4-0.6: 0.002-0.003: 0.5-0.
55. The heating rate during the polymerization reaction is 3°C / min-10°C / min. The polymerization reaction time is 2.5h-3.5h. After the polymerization reaction, the following treatments are also included: grinding, washing and drying the reaction product; the washing is washing with water and anhydrous ethanol in sequence, and the drying is vacuum drying at 60°C for 12h.
6. The method for preparing poly(cobalt phthalocyanine) having a defective structure according to any one of claims 1 to 3, characterized in that: The ratio of the polyphthalocyanine cobalt to water is 200 mg to 300 mg: 30 mL to 50 mL, the mixing time is 15 min to 25 min, and the mixing is carried out under stirring conditions; the hydrothermal reaction also includes the following treatments: washing and drying the reaction product; the washing is carried out using water or anhydrous ethanol, and the drying is carried out at 60° C. in vacuum for 12 hours.
7. A poly(cobalt phthalocyanine) having a defective structure obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the poly(cobalt phthalocyanine) with defective structure as claimed in claim 7 in treating wastewater with organic pollutants.
9. The use according to claim 8, characterized in that: The method comprises the following steps: mixing polyphthalocyanine cobalt with defective structure and organic pollutant wastewater, adding persulfate to carry out degradation reaction, and realizing degradation of organic pollutants in water; the ratio of polyphthalocyanine cobalt with defective structure to organic pollutant wastewater is 0.03g-0.2g:1L.
10. The use according to claim 9, characterized in that: The amount of persulfate added is 0.75mmol to 1.25mmol per liter of organic pollutant wastewater, the persulfate is potassium persulfate, the concentration of organic pollutants in the organic pollutant wastewater is ≤20mg / L, the pH value of the organic pollutant wastewater is 3 to 11, the organic pollutants in the organic pollutant wastewater include at least one of antibiotics and dyes, the antibiotic is at least one of tetracycline hydrochloride, levofloxacin hydrochloride, ciprofloxacin and phenol, the dye is at least one of rose red B and methylene blue, the degradation reaction time is ≥5min, the degradation reaction is carried out under stirring conditions, and the stirring speed is 300rpm to 500rpm.
Citation Information
Patent Citations
Preparation method of polynuclear metal phthalocyanine alkane oxidation catalyst
CN102850359A
Polyphthalocyanine nano material capable of catalyzing conversion of carbon dioxide efficiently as well as preparation method and application of material
CN107915841A
Solid-phase synthesis method of metal phthalocyanine compound
CN110128431A
Monatomic cobalt-loaded tubular carbon nitride catalyst as well as preparation method and application thereof
CN114534759A
Bismuth telluride / polyphthalocyanine cobalt composite material and preparation method and application thereof
CN118231613A
